READING ALOUD ABILITY IN LEARNING LONTARAQ ACCIDENTS STUDENTS OF SDN 180 SIKKOJANG DISTRICT SOPPENG - Arfiana, Arfiana; Agussalim, Andi; Nurhusna, Nurhusna (Media Inovasi Pendidikan dan Publikasi, 2025)
This research is a quantitative descriptive study which aims to describe the ability to read aloud in learning the lontaraq script of students at SDN 180 Sikkojang, Soppeng Regency. In this study, the entire population came from students at SDN 180 Sikkojang, Soppeng Regency academic year 2024/2025. Sampling in this research was carried out using total sampling. The data collection technique in this research was the oral test technique. The data obtained was then analyzed using quantitative descriptive. There are four criteria for assesment aspects in this research, including the fluency aspect, the use of intonacion aspect, the accuracy of pronunciation aspect, and the volume aspect of the voice. In the aspect of fluency, only 2 students (13%) obtained a score of 70 and above, while in the aspect of intonation use, only 1 student (7%) achieved that score. Furthermore, in the aspect of precise pronunciation, there was 1 student (7%) and in the aspect of voice volume, only 2 students (13%) managed to obtain a score of 70 and above.